2017
DOI: 10.1002/iub.1693
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body fat percentage change on future diabetes in subjects with normal glucose tolerance

Abstract: The aim of the work was to determine the effect of body fat change on risk of diabetes in normal glucose tolerance (NGT) population. A total of 1,857 NGT subjects were included and followed up for an average period of 44.57 months. Body fat percentage (BF%) was measured by bioelectrical impedance analysis. Subjects were grouped based on the BF% and/or body mass index (BMI) state. Among all subjects, 28 developed diabetes after follow-up. Compared with subjects with stable normal BF% (control), subjects who bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
2
10
0
2
Order By: Relevance
“…In addition, we found that overweight people with normal BF% did not have an increased risk of diabetes (HR: 0.441, 95% CI 0.101-1.928, p = 0.232). The results agree with those of Zhao et al 10 , who found that those with stable normal BF% and abnormal BMI did not have a significantly higher risk of developing diabetes (RR = 2.838, 95% CI 0.293-27.537). The possible existence of healthy obesity has been a subject of debate for many years because some overweight and obese individuals are found to have a metabolically healthy status 13 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found that overweight people with normal BF% did not have an increased risk of diabetes (HR: 0.441, 95% CI 0.101-1.928, p = 0.232). The results agree with those of Zhao et al 10 , who found that those with stable normal BF% and abnormal BMI did not have a significantly higher risk of developing diabetes (RR = 2.838, 95% CI 0.293-27.537). The possible existence of healthy obesity has been a subject of debate for many years because some overweight and obese individuals are found to have a metabolically healthy status 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results from the current study are similar to a previous Chinese cohort study in which Zhao et al conducted a community-based study of 1857 normal glucose tolerance subjects that were followed for 44.57 months. Compared with individuals having normal BF% and BMI, subjects with normal BMI but increased BF% had a higher risk of developing diabetes (Relative risk [RR]: 4.790, 95% CI 1.061-21.621) 10 . Differences in RRs between Zhao et al and our study might be due to differences in study design, duration of follow up, control group, and baseline metabolic state of the subjects included.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being widely used as a surrogate measure of obesity, BMI underestimates the prevalence of obesity, defined as an excess of body fat . Indeed, clinical studies have demonstrated that the actual body fat amount is playing an essential role in the development of insulin resistance and that maintaining normal body fat is significantly more relevant than BMI in preventing diabetes . Several epidemiological studies have confirmed that BMI alone may lack predictive value for type 2 diabetes due to differences in muscle mass and fat mass (particularly abnormal adiposity) for the same BMI value .…”
Section: Diabetes and Body Fat: A Long‐standing Liaisonmentioning
confidence: 99%
“…However, the use of BMI entails several limitations since body fat content is insufficiently captured by BMI. High body fat percentage (BF%), often defined as ≥ 35% in women, is reported in up to 50% of the population with a BMI within the non-obese range [2][3][4][5] and is linked to worse metabolic parameters [3,6] including disturbed glucose metabolism [7] and future risk of type 2 diabetes [8].…”
Section: Introductionmentioning
confidence: 99%